EFFECTIVENESS OF THE EXPANSION PROGRAM OF EMPLOYMENT OPPORTUNITY FOR UNEMPLOYMENT PREVENTION OF SUKABUMI DISTRICT - Dilla Novita; Yana Fajar FY Basori; Andi Mulyadi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
The purpose of this study to determine the effectiveness of the expansion of employment opportunities program against unemployment reduction in Sukabumi. The method used is qualitative method with descriptive approach. Data collection using observation techniques, interviews, and documentation. Data analysis using Flow model Method and Data Validation using triangulation technique. This study uses the theory of program effectiveness from Sutrisno with 5 indicators of program effectiveness, namely program understanding, target accuracy, timeliness, achievement of goals, and taking real research results show the effectiveness of the expansion of Employment Opportunities Program Against Unemployment in Sukabumi runs well where the dimension of understanding the independent labor program. Program runs skill training through the P2KSS program so as to support the achievement of targets. On the dimension of the accuracy of the target where the independent labor program according to the target where targeting housewives. In imensi keteapatan socialization time will be quite effective independent work program because it has done socialization as much as 2 times face to face. In the dimension of the program where the independent labor program spreads widely to all levels of society. And in the dimension of real decision where Disnakertrans provide facilities and assistance to the community and also training has been implemented.